After austerity: Measuring the impact of a job guarantee policy for Greece - Rania Antonopoulos; Sofia Adam; Kijong Kim; Thomas Masterson; Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 2014)
To mobilize Greece's severely underemployed labor potential and confront the social and economic dangers of persistent unemployment, we propose the immediate implementation of a direct public benefit job creation program - a Greek "New Deal." The Job Guarantee (JG) program would offer the unemployed jobs, at a minimum wage, on work projects providing public goods and services. This policy would have substantial positive economic impacts in terms of output and employment, and when newly accrued tax revenue is taken into account, which substantially reduces the net cost of the program, it makes for a comparatively modest fiscal stimulus. At a net cost of roughly 1 percent to 1.2 percent of GDP (depending on the wage level offered), a midrange JG program featuring the direct creation of 300,000 jobs has the potential to reduce the unemployed population by a third or more, once indirect employment effects are taken into account. And our research indicates that the policy would do all this while reducing Greece's debt-to-GDP ratio - which leaves little room for excuses.
Keywords: 330